Motives for child homicide by mothers incarcerated in four correctional centres in South Africa - Malope, N. F. (My University, 2014)
The aim of the current study was to explore and describe the views on child homicide by mothers. The qualitative research approach, and in particular the phenomenological method of inquiry was used. A sample of seventeen mothers (with ages ranging from thirteen to fifty three years) was drawn from four female correctional centres in South Africa, namely; Thohoyandou (Limpopo Province), Polokwane (Limpopo Province), Johannesburg correctional centre (Gauteng Province) and Durban Westville correctional centre (KwaZulu-Natal Province). The sample was obtained through purposive sampling. All the participants were interviewed using in-depth semi-structured interviews. Data were analyzed using the phenomenological method. The themes that emerged from data analysis were: a) Motives for child homicide; b) Type of methods used in child homicide; and, c) Pre- and post-homicidal ideations and behaviour. The study revealed that there were different motives leading mothers to commit child homicide. These included: child homicide as a result of everyday stressors that the mothers encountered;child homicide as an act of altruism; child homicide to gain acceptance; perpetrators of child homicide as victims of abuse; child homicide as accidental; child homicide attributed to witchcraft; and, mental illness as amotive for child homicide. The study also highlighted different types of methods used by the mothers to commit child homicide. The methods included: the use of weapons; hitting, dropping and strangling; suffocation; drowning; and, poisoning. The findings also suggested that pre-homicidal ideations and behaviour of the participants were associated with anger, depression, frustration and self blame. The participants showed post-homicidal ideations and behaviour such as remorse, regret and guilt, whilst others felt a sense of relief and were somehow hopeful about the future. The study is concluded by making recommendations for further research on child homicide based on larger samples.
Thesis (M.A. (Psychology)) -- University of Limpopo
Keywords: Child homicide; Women murderers; 364.152082; Women murderers -- South Africa; Child abuse; Homicide -- South Africa